Clinicopathological significance of 'atypical ductal proliferation' in core needle biopsy of the breast. (February 2014) - Abe, Eriko; Suzuki, Koyu; Hayashi, Naoki; Yang, Yang; Chih‐Ping, Li; Uno, Mieko; Akiyama, Futoshi; Yamauchi, Hideko; Nakamura, Seigo; Tsugawa, Koichiro; Tsunoda, Hiroko; Ohde, Sachiko; et al.
<x xml:space="preserve">Abstract</x> Atypical ductal proliferation or ADP has been used in histopathological diagnosis of core needle biopsy (CNB) but its details have not been well studied. Therefore, we examined the clinicopathological characteristics of the initial CNB cases diagnosed as 'ADP ' who subsequently turned out to be malignant, and compared the findings to those that did not. Among 101 cases initially diagnosed as ADP in CNB, the second biopsy revealed no carcinoma (38), ductal carcinoma in situ (DCIS) (45) and invasive carcinoma (18). Significant differences were detected between those which turned out to be carcinoma and those that did not, in the status of myoepithelial cells identified by p63 immunohistochemistry (P = 0.026) and ultrasound (US) categories (P < 0.001). We further compared the histopathological characteristics of those initially diagnosed as ADP and subsequently as DCIS or invasive ductal carcinoma (IDC) with those initially diagnosed as such. DCIS or IDC cases initially diagnosed as ADP had significantly lower Ki67 labeling index (P < 0.01, P < 0.01) and histological grade using Van nuys prognostic index (P < 0.01) or Nottingham histological grades (P < 0.01) respectively than those initially as DCIS or IDC. An assessment of myoepithelial components with US findings might contribute to determine the subsequent clinical algorithm of the patients diagnosed as ADP at initial CNB.